2021
DOI: 10.1021/acsnano.1c02178
|View full text |Cite|
|
Sign up to set email alerts
|

Graphitization with Suppressed Carbon Loss for High-Quality Reduced Graphene Oxide

Abstract: An efficient reduction method to obtain high-quality graphene sheets from mass-producible graphene oxide is highly desirable for practical applications. Here, we report an in situ deoxidation and graphitization mechanism for graphene oxide that allows for high-quality reduced graphene oxide sheets under the low temperature condition (<300 °C) by utilizing a well-known Fischer–Tropsch reaction catalyst (CuFeO2). By applying modified FTR conditions, where graphene oxide was reduced on the catalyst surface under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The reduction of rGO induced by the corresponding oxidation of Fe in the Fe 3 O 4 @rGO‐65 composite, with high binding energy of an oxygen atom, was further verified by XPS analysis (Figure 3b–e) [42] . In the high‐resolution C1s XPS spectra of pristine rGO and Fe 3 O 4 @rGO‐65 (Figure 3b), the shift of the deconvoluted peaks to lower binding energies in COOH, C−O, and C=O of Fe 3 O 4 @rGO suggests deoxygenation of rGO [40,43,44] .…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The reduction of rGO induced by the corresponding oxidation of Fe in the Fe 3 O 4 @rGO‐65 composite, with high binding energy of an oxygen atom, was further verified by XPS analysis (Figure 3b–e) [42] . In the high‐resolution C1s XPS spectra of pristine rGO and Fe 3 O 4 @rGO‐65 (Figure 3b), the shift of the deconvoluted peaks to lower binding energies in COOH, C−O, and C=O of Fe 3 O 4 @rGO suggests deoxygenation of rGO [40,43,44] .…”
Section: Resultsmentioning
confidence: 64%
“…The reduction of rGO induced by the corresponding oxidation of Fe in the Fe 3 O 4 @rGO-65 composite, with high binding energy of an oxygen atom, was further verified by XPS analysis (Figure 3b-e). [42] In the high-resolution C1s XPS spectra of pristine rGO and Fe 3 O 4 @rGO-65 (Figure 3b), the shift of the deconvoluted peaks to lower binding energies in COOH, CÀ O, and C=O of Fe 3 O 4 @rGO suggests deoxygenation of rGO. [40,43,44] Meanwhile, in the high-resolution Fe2p XPS spectrum (Fig- ure 3c-e and Figure S6), the Fe2p 3/2 (711.28 eV) and Fe2p 1/2 (724.94 eV) peaks of Fe 3 O 4 @rGO-65, corresponding to the magnetite phase, appeared at higher binding energies compared to Fe 3 O 4 prepared without rGO, demonstrating additional oxidation of Fe 3 O 4 on the rGO sheets.…”
Section: Synthesis and Physical Characterizationmentioning
confidence: 98%
“…In a similar way, rGO for Ni(II) removal was obtained using Tecoma stans leaf extract to reduce GO [ 135 ]. Finally, in a recent work, a catalytic reduction process to obtain a very high-quality rGO was reported [ 134 ]. In this case, the use of a Fischer–Tropsch catalyst in the absence of hydrogen allowed it to operate at the very low temperature of 250 °C, with oxygen as the only byproduct.…”
Section: Greener Alternatives To Traditional Graphitization For Cnm P...mentioning
confidence: 99%
“…have reported in situ deoxygenation and graphitization of GO using Fischer–Tropsch reaction catalyst (CuFeO 2 ) to obtain high‐quality few‐layered (5–10 layers) RGO with an I D / I G ratio of 0.19 and a crystallite size of 95.57 nm. [ 21 ] Yet, the total process time can be longer, as 12 h, involving several steps. Voiry et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yoon et al have reported in situ deoxygenation and graphitization of GO using Fischer-Tropsch reaction catalyst (CuFeO 2 ) to obtain high-quality few-layered (5-10 layers) RGO with an I D /I G ratio of 0.19 and a crystallite size of 95.57 nm. [21] Yet, the total process time can be longer, as 12 h, involving several steps. Voiry et al has reported a microwave-assisted reduction of GO into high-quality RGO with a lower I D /I G ratio, a large crystallite size (180 nm), and a large distance between defects (38 nm).…”
mentioning
confidence: 99%